Tra Zehnder : iban woman patriot of Sarawak - Hew, Cheng Sim; Rokiah, Talib (Universiti Malaysia Sarawak, (UNIMAS), 2011)
There has been a resurgence of interest in the use of the life history method in social science research. This particular qualitative research method has grown in significance with the realization that an understanding of history and broader societal changes through people's 'lived experiences' is important and often much neglected. An individual is not an isolated entity but is enmeshed in a network of social relations and institutions. Thus, by placing the life of an individual centre-stage, the intimate and the personal reveal the public and the political at a specific point in history. The feminist notion of "the personal is political" takes on a new meaning in the use of the life history method. In choosing to write the life history of Philomena Tra Zehnder we are informed by our feminist stance of highlighting women's lives and giving space to the life stories of minority groups which are often sidelined and ignored. This book is the first of its kind to be written about an Iban woman leader in Sarawak. This is not merely to valorize Dato Seri Philomena Tra Zehnder but it is hoped that in reading her life story, one would also have a glimpse of the historical developments connected with her life and times.